MODEL PEMBELAJARAN BERBASIS PROYEK TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA MATERI KOLOID - Kumalasari, Desy; Milama, Burhanudin; Bahriah, Evi Sapinatul (LPPM Universitas Negeri Jakarta, 2017)
The aim of this study was to determine the influence of Project Based Learning on creative thinking skills of student on colloid concept. The method used in this study was quasi experiment with non-equivalent control group design. The population in this study was second semester students of SMAN 5 in Bekasi of Academic Years 2014/2015. Samples are class XI MIA-4 as the experimental class (given treatment by project-based learning model), and class MIA XI-2 as the control class (given treatment by lecture method). Data collection techniques were gained through an essay test instrument. Data value of the average pretest-posttest control group and experimental group were analyzed using t-test. The average of pretest score for control class is 19.89 and experiment class is 18.11, while the average of postest score of control class is 24.5 and experimental class is 29.35. The t-test result showed that tcount (7.35) was greater than ttable (2.0049) with significance level 5%, so the research hypothesis which states that there are significant influence of project-based learning to the creative thinking skills of students on colloid concept are accepted. In order to obtain the greatest number of information about creative thinking skills, when implemented project based learning must consider several things, that are: time management, formulation of the problem, step of project work, and assessment systems should be informed to the students in a clear and focused so that students can understand and have a passion in running the project. Keywords: Project Based Learning, Creative Thinking, Colloid.